1999
DOI: 10.1523/jneurosci.19-19-08172.1999
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Enhances Central Olfactory Neuron Responses to Female Sex Pheromone in the Male Sphinx MothManduca sexta

Abstract: In the brain of the sphinx moth Manduca sexta, sex-pheromonal information is processed in a prominent male-specific area of the antennal lobe called the macroglomerular complex (MGC). Whole-cell patch-clamp recordings from identified projection (output) neurons in the MGC have shown that serotonin [5-hydroxytryptamine (5-HT)] increases both the excitability of MGC projection neurons and their responses to stimulation with pheromone. At least two types of voltage-activated potassium currents in these cells are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
123
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(130 citation statements)
references
References 63 publications
(90 reference statements)
6
123
1
Order By: Relevance
“…Similarly, the serotonergic effects might result from the modulation of chordotonal sensillae, or of other sensory cells, by serotonin (e.g. Ramirez and Orchard, 1990;Kloppenburg et al, 1999) in a way mimicking and potentiating pymetrozine effects.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the serotonergic effects might result from the modulation of chordotonal sensillae, or of other sensory cells, by serotonin (e.g. Ramirez and Orchard, 1990;Kloppenburg et al, 1999) in a way mimicking and potentiating pymetrozine effects.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological and behavioral effects of 5HT on the olfactory system of moths have been extensively studied and it has been suggested that 5HT acts as a circadian modulator of olfactory sensitivity (Kloppenburg et al, 1999;Gatellier et al, 2004). In the AL of M. sexta, 5HT increases the excitability of intrinsic neurons by reducing two potassium conductances (Kloppenburg et al, 1999) and so to begin to study the cellular mechanisms by which 5HT has this effect, we cloned the 5HT receptors from M. sexta.…”
Section: Cloning and Sequence Analysis Of Ms5ht1a And Ms5ht1bmentioning
confidence: 99%
“…In the AL of M. sexta, 5HT increases the excitability of intrinsic neurons by reducing two potassium conductances (Kloppenburg et al, 1999) and so to begin to study the cellular mechanisms by which 5HT has this effect, we cloned the 5HT receptors from M. sexta. We found that while both of the Ms5HT1 receptors contain amino acid residues characteristic of 5HT receptors, they differ significantly in their amino-terminal and 3rd cytoplasmic loop region, which indicates that they are two distinct receptors.…”
Section: Cloning and Sequence Analysis Of Ms5ht1a And Ms5ht1bmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that it may influence olfactory learning in honey bees (Mercer and Menzel, 1982) and modulate the sensitivity and excitability of projection neurons in the antennal lobes of the moth Manduca sexta (Mercer et al, 1995;Kloppenburg et al, 1999).…”
Section: Introductionmentioning
confidence: 99%